2021
DOI: 10.3390/s21227453
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Mirror for Emotion Monitoring in Home Environments

Abstract: Smart mirrors are devices that can display any kind of information and can interact with the user using touch and voice commands. Different kinds of smart mirrors exist: general purpose, medical, fashion, and other task specific ones. General purpose smart mirrors are suitable for home environments but the exiting ones offer similar, limited functionalities. In this paper, we present a general-purpose smart mirror that integrates several functionalities, standard and advanced, to support users in their everyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…On the one hand, currently available technologies have expanded the repertoire of ES techniques [ 113 , 114 , 115 ] offering novel possibilities; mobile devices are one such example [ 113 , 116 , 117 ]. Among others, devices that are likely to play a key role in the near future are smart mirrors [ 118 , 119 ]. Unfortunately, in most cases, researchers conducting experiments with novel devices adapted paper-and-pencil methods from classic ES sampling studies [ 114 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, currently available technologies have expanded the repertoire of ES techniques [ 113 , 114 , 115 ] offering novel possibilities; mobile devices are one such example [ 113 , 116 , 117 ]. Among others, devices that are likely to play a key role in the near future are smart mirrors [ 118 , 119 ]. Unfortunately, in most cases, researchers conducting experiments with novel devices adapted paper-and-pencil methods from classic ES sampling studies [ 114 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most advanced studies, the ES procedure is extended to exploit physiologically-triggered probing and recording of participants’ self-reports and peripheral physiological activity [ 121 ]. The adoption of devices such as smart mirrors [ 118 , 119 ], beyond the privacy concerns that we shall not address here, might offer the availability of multimodal data for subsequent analysis; in addition, these more complex interaction devices seem to have potential for longitudinal studies in the field under quasi-experimentation design [ 117 ] based on interval contingent triggering (e.g., interacting with the mirror twice a day) [ 116 ]. In the case of current ES studies, ratings to be evaluated are by and large self-reported; however, as long as we have time-series, the presented methods can be suitably adapted for gauging recurrent patterns and their variability together with indicators of affective/social states, namely that crystallise the bare essentials of ES [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…In [10], the author proposed a model for a smart mirror called the Smart eHealth Mirror. The mirror is designed to detect health issues by analysing the posture and body changes of the individual using a new algorithm called the Posture Analyse Algorithm (PAA).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Smart mirrors are devices designed to interact with users in a different way. They are often based on the Internet of Things (IoT) concept and allow users to interact with applications using touch or voice controls and to display feedback and various information [ 15 ].…”
Section: Introductionmentioning
confidence: 99%